Intensive Arabic Language Program to Strengthen the Reading Ability of New Arabic Language Education Students - Ratna Sa'idah; Patria Ayudha Putri; Fatma Fitriana; Umar Faruq; Eko Budi Hartanto (Asalibuna, 2022)
This study aims to find out how the application of the intensive class program to prepare the maharah qiroan 1 course for new students of the Arabic Language Education study program. By knowing this application, new students of the Arabic Language Education study program are able to prepare to take the qiroah 1 course in the next semester. This research uses a qualitative approach with a descriptive type. Data collection techniques use interviews, observation and documentation. The results showed that the intensive Arabic program was carried out 4 consecutive days for one semester and spent 21 dars. When learning the TAM program using the mubasyaroh method and communicative approach, the results of improvement and positive impact are shown on the scores of the placement test and post test. The average placement test score is 56% and the post test score is 65%, an increase of 9%. The advantages of the TAM program are being able to understand basic Arabic in a short time, improving Arabic language skills, facilitating the teaching and learning process, motivating students in the spirit of learning Arabic, increasing student confidence because TAM classes are adjusted to the level of ability of each student, showing more student learning results. Furthermore, the disadvantage of the TAM program is the factor of students who feel bored at the end of lectures, from the factor of books, patterns, texts or sentences used in learning TAM and maharah qiroah 1, there are significant differences so that it is difficult to understand according to new students.